Exploration of final year students' and academicians' views on liberalisation of provisionally-registered pharmacists' (PRP) training / Muhammad Al-qasim Mohammad Nasir - Mohammad Nasir, Muhammad Al-qasim (2014)
Background: A new liberalization policy has been implemented since 2012 that liberalizes the training of provisionally-registered pharmacists (PRPs) in Malaysia. This means pharmacy graduates are now allowed to do their pre-registration training at places other than the already saturated government hospitals. So far, the perceptions and views of pharmacy students and academicians regarding this liberalization are yet to be explored. Objectives: This study attempted to explore the general views of students and academicians on the liberalization policy. Methods: Data were collected through online mini-survey and interviews. The online survey was conducted using Survey Monkey online survey platform and analyzed using simple descriptive statistics. Semi-structured interviews were conducted and all face-to face and phone interviews were audio recorded and transcribed verbatim. For interviews conducted via facebook chat, the online conversation was saved. The transcripts were analyzed using framework analysis. Results: The majority of final-year students (77%) who responded to the online survey answered that they prefer to go to government hospitals for their PRP training. As for the interview, the main themes that were identified after analysis had been performed